The clinical burden of extremely preterm birth in a large medical records database in the United States: complications, medication use, and healthcare resource utilization. (30th December 2022) - Siffel, Csaba; Hirst, Andrew K.; Sarda, Sujata P.; Chen, Hong; Ferber, Jeannette; Kuzniewicz, Michael W.; Li, De-Kun
Abstract: Introduction: Approximately 5% of global preterm births are extremely premature (EP), defined as occurring at less than 28 weeks gestational age. Advances in care have led to an increase in the survival of EP infants during the neonatal period. However, EP infants have a higher risk of developing complications such as bronchopulmonary dysplasia (BPD), intraventricular hemorrhage (IVH), and retinopathy of prematurity (ROP). BPD and other respiratory morbidities are particularly prevalent among this population. To understand the healthcare resource utilization (HRU) of EP infants in the United States, the clinical and economic burden of extreme prematurity was examined in this retrospective study of data extracted from electronic medical records in the Kaiser Permanente Northern California (KPNC) health system. Methods: The analysis included data from EP infants live-born between January 1997 and December 2016, and focused on complications and HRU up to 3 years corrected age (CA), covering the period up to December 2018. Stillbirths, infants born at <22 weeks gestational age, and infants with major congenital malformations were excluded. Complications of interest (BPD, IVH, and ROP) and medication use were compared by age group (≤1 year, >1 year and ≤2 years, and >2 years and ≤3 years CA). Analysis of HRU included hospital readmissions, ambulatory visits, and emergency room (ER) visits. Results: A total of 2154 EP births (0.32% of total live births and 4.0% of preterm births that met the inclusion/exclusion criteria) were analyzed. The prevalence of EP birth showed a declining trend over time. ROP was the most commonly recorded complication during the birth hospitalization (37.1% any stage; 2.9% Stages 3 and 4). BPD was recorded in 34.3% of EP infants. IVH (any grade) was recorded in 22.7% of EP infants (6.4% Grades III and IV). A majority (78.7%) of EP infants were diagnosed with at least one respiratory condition during the first year CA, the most common being pneumonia (68.9%); the prevalence of respiratory conditions decreased over the second and third years CA. During the first 3 years CA, the most common medications prescribed to children born EP were inhaled bronchodilators (approximately 30% of children); at least 15% of children received systemic corticosteroids and inhaled steroids during this period. During the first 3 years CA, at least one hospital readmission was recorded for 16.4% of children born EP; 57.1% of these readmissions were related to respiratory conditions. At least one ER visit was recorded for 33.8% of children born EP, for which 53.1% were due to a respiratory condition. Ambulatory visits were recorded for 54.2% of EP children, for which 82.9% were due to a respiratory condition. Conclusions: The short- and long-term clinical burden of EP birth was high. The onset of BPD, IVH, and ROP was common during the birth hospitalization for EP infants. Medication use, hospital readmission, and clinic visits (ER and ambulatory) occurred frequently in these children during the first 3 years CA, and were commonly due to respiratory conditions. Strategies prioritizing the reduction of risk and severity of respiratory conditions may alleviate the clinical burden of EP birth over the long term.